Oxidative status among a group of pregnant women in relation to gingival health condition - Sarar N Al Najjar; Baydaa Hussein (College of Dentistry/ University of Baghdad, 2019)
Background: pregnancy as a systemic condition causes changes in the functioning of human body as a whole and specifically in the oral cavity and it also is considered as a stressful condition. These changes may favor the increase of oxidative stress. Aim: The aim of this study was to estimate the level of marker of oxidative stress (malondialdehyde) and antioxidant (uric acid) in saliva of pregnant compared to non-pregnant women and to assess the gingival health condition in both groups. Additionally, unstimulated salivary flow rate was determined in both groups. Subjects, materials and methods: The study group consisted of sixty pregnant women, they were divided into three equal groups according to trimester (20 pregnant women for each trimester), and they were selected randomly from the Maternal and Child Health Care Centers in Baghdad city, their age range was 20-25 years. In addition to 60 newly married non-pregnant women as a control group and matched with age. Collection of unstimulated salivary samples was carried out under standardized conditions. Dental plaque and gingival indices were used for recording the oral hygiene and gingival health respectively. Salivary flow rate was measured then salivary samples were analyzed to determine the level of salivary antioxidant (uric acid) and lipid peroxidation biomarker of oxidative stress (malondialdehyde). Result: The data analysis of the present study found that the level of salivary malondialdehyde was higher among pregnant women compared to non-pregnant controls with statistically significant difference (p<0.05), while salivary uric acid was statistically significantly lower among the pregnant women compared to non-pregnant controls (p<0.05). Salivary analysis demonstrated that the salivary flow rate was statistically significantly lower among the pregnant women compared to non-pregnant controls (p<0.05). The values of plaque and gingival indices were higher among pregnant women compared to non-pregnant controls with statistically significant difference (p<0.05). The correlation of gingival index with plaque index in study and control group was significant (p<0.05), while with others variables were non-significant (p>0.05). Conclusion: The current study showed an increase in oxidative status in saliva during pregnancy that could affect gingival health which was also affected by oral hygiene.